“I can see where they're coming from, but when you're on the end of it . . . you just want to get the money and the drug.”: Explaining reactions to explicit healthcare rationing. - Owen-Smith, Amanda; Coast, Joanna; Donovan, Jenny (Social Science & Medicine, 2009)
The traditional pattern of implicit and unacknowledged rationing in the UK National Health Service (NHS) is beginning to change. The advent of the National Institute for Health and Clinical Excellence (NICE), widespread use of the Internet, and the media interest in healthcare rationing means that patients are increasingly likely to be knowledgeable about their healthcare, and to learn that treatments are not available for financial reasons. However, lack of empirical research in this area means that how patients react to explicit rationing is unknown, and thus its outcomes are largely the matter of conjecture. This paper presents results from a UK qualitative interview study with patients who have experienced rationing associated with morbid obesity or breast cancer care, and related NHS managers and clinicians. In total, 31 patients and 21 healthcare professionals were interviewed, although only 21 patients knew that their treatment had been subject to rationing. Purposive and theoretical sampling methods were used to ensure a diverse sample of patients, and data were analysed using methods of constant comparison. Patients had a choice about whether to accept explicit rationing decisions, protest against them, or pay for private care. However, the accounts of many patients showed there was a gulf between their general views around the necessity of rationing and how they said they would react to such decisions in theory, and how they stated they actually reacted when faced with shortages affecting their own treatment. Among the most important factors affecting how patients reacted to rationing were their sense of entitlement to NHS care, and the attitude of the clinical team providing treatment. The findings suggest that patients need to be provided with sufficient information and support to make an informed decision following the revelation of rationing, and that clinicians need training to assist them in communicating rationing decisions. Copyright (c) 2009 Elsevier Ltd.